Anaerobic Co-Digestion of Human Excreta and Corn Stalk for Biogas Production - Agus Hadiyarto; Dyah Ayu Pratiwi; Aldila Ayu Prida Septiyani (Reaktor, 2019)
The anaerobic decomposition process of human feces substrate with a C/N ratio of 14.6 has failed to produce biogas optimally. In order to produce biogas maximally, the C/N ratio in the substrate should be in the range of 20-30. In this study, a combination of human feces substrate (C / N = 14.6) with corn stalk waste (C / N = 66.5) was carried out. Corn stalks were soaked first in a NaOH solution to separate lignin before being mixed with human feces. In this study the effect of the C/N ratio from the combination of feces and corn stalks as well as the effect of the type of activated sludge on the rate of biogas production were evaluated. The C/N ratios were varied at 20, 25, and 30 with F/M of 0.5. As the source of microbes is the activated sludge of human feces. A further experiment was carried out by varying the types of microbes where sludge from cow's rumen, activated sludge from feces, and activated sludge from rotten corn stalk was employed at a C/N ratio of 30 and F/M of 0.5. The results of this study showed that the optimal biogas production was obtained at a C/N ratio of 30 with a cumulative gas volume of 13.185 ml for 60 days. The type of microbes that produce maximum biogas production was the activated sludge from the rumen. The optimum biogas yield was obtained at 4.184 liters/kg COD, which was achieved in the stationary phase with a C/N ratio of 30.Keywords: anaerobic co-digestion; biogas; corn stalk; human feces